The Affordable Care Act: policy predictors of integrated care between Hispanic-serving and mainstream mental health organizations - Robert Rosales; Rocío Calvo (BMC, 2021)
Abstract Background The Patient Protection and Affordable Care Act increased funding for integrated care to improve access to quality health care among underserved populations. There is evidence that integrated care decreases inequities in access and quality of mental health care among Hispanic clients. Increasing integrated care at Hispanic-Serving Organizations may help to eliminate mental health service disparities among Hispanic clients. Method Using organizational responses from the 2014 and 2016 waves of the National Mental Health Service survey, this study conducted multivariate logistic analyses to assess whether the ACA policies related to integrated care increased the provision of integrated addictions treatment and primary care at mental health Hispanic-Serving Organizations, relative to Mainstream Organizations. Results Findings showed that Hispanic-Serving Organizations (54.4%) were less likely to provide integrated health services than Mainstream Organizations (59.1%) after the ACA. However, federal funding to help organizations transition into integrated care services (AOR = 1.74, p = 0.01) and accepting Medicaid payments (AOR = 1.59, p = 0.01) increased the provision of integrated care services at Hispanic-Serving Organizations over time. Conclusions Health care policies that increase funding to adopt integrated health services at community Hispanic-Serving Organizations may help decrease inequities in mental health access for Hispanics in the United States.